2006
DOI: 10.1002/ajmg.a.31100
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmune idiopathic hydrops fetalis and congenital lymphatic dysplasia

Abstract: Six newborns that presented at birth with nonimmune hydrops fetalis and for whom no cause could be found were investigated for the presence of lymphatic dysplasia. Careful analysis led to findings of some degree of lymphatic dysplasia in all patients. This suggests that lymphatic dysplasia may represent at least part of the causes that are responsible for the "idiopathic" form of nonimmune hydrops fetalis. Carefully searching for lymphatic dysplasia in these patients, and if indicated in their relatives, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This is also evident in the percentage of cases assigned to the Lymphatic dysplasia category which showed a remarkable increase in the present review compared to the previous review. The recent literature describing the relationship between NIHF and congenital lymphatic dysplasia may well have led to increased awareness of the role of lymphatic system disorders in NIHF [Rodríguez et al, Bellini et al, , ; Randenberg , ; Bellini and Hennekam, ; Désilets and Audibert, ]. Indeed, assigning patients with, for instance, Turner syndrome to the Lymphatic dysplasia category may have led to a further decrease in the Chromosomal category.…”
Section: Discussionmentioning
confidence: 99%
“…This is also evident in the percentage of cases assigned to the Lymphatic dysplasia category which showed a remarkable increase in the present review compared to the previous review. The recent literature describing the relationship between NIHF and congenital lymphatic dysplasia may well have led to increased awareness of the role of lymphatic system disorders in NIHF [Rodríguez et al, Bellini et al, , ; Randenberg , ; Bellini and Hennekam, ; Désilets and Audibert, ]. Indeed, assigning patients with, for instance, Turner syndrome to the Lymphatic dysplasia category may have led to a further decrease in the Chromosomal category.…”
Section: Discussionmentioning
confidence: 99%
“…Bellini et al suggested that lymphatic dysplasia may at times account for the “idiopathic form” of HF. Ghalamkarpour et al supported this, highlighting a mutation in 2 lymphagiogenic genes in 3 idiopathic NIHF cases (VEGFR3 and FOXC2).…”
Section: Discussionmentioning
confidence: 99%
“…The central disturbance is a low output failure of the lymphatic system, that is, the overall lymphatic transport is reduced. This derangement occurs not only in lymphatic dysplasias but also in increased central venous pressure, as this causes difficulties in draining the lymph into venous circulation as well [Bellini et al, 2006b].…”
Section: Discussionmentioning
confidence: 99%